ELEMENTS OF POWER GRID DESIGN - Khamidjonov Zuhriddin Marufjon ugli (Scholar Express Journals, 2021)
Designing a new power grid is a complex task that requires solving many technical and economic issues. At the technical issues that given for designing,piece of consumer loads with reliability of energy supply is provided . It also provides opportunities for further development of the network, such as daily schedules of loads, operating time per year with maximum load, secondary voltage of substations, relative position to each other, and availability of supply sources.
Keywords: Rated voltage, economic current density, overhead line, substation, transformer